UMP Technical Staff produce tutorial videos as T L aid - Nor Salwana, Mohammad Idris (2021)
PEKAN, 12 January 2021 – The COVID-19 pandemic has affected teaching and learning (T&L) with the use of online applications as the new norms for learning.